BOOK REVIEW OF ONE NIGHT WITH PRINCE CHARMING WRITTEN BY ANNA DEPALO - Rostanti, Diana (LANTERN (Journal on English Language, Culture and Literature), 2015)
According to Wellek and Warren (1976: 94) in Theory of Literature, literature represents life and life is, in large measure, a social reality, even though the natural word and the inner or subjective world of the individual have also been objects of literary ‘imitation’. Novel is very popular among literature enthusiasts. The story within a novel usually reflects human life, so the readers will understand the moral message behind the story.